PENGARUH MAKE A MATCH PUZZLE TERHADAP KETERAMPILAN BERPIKIR KRITIS TINJAUAN SELF EFFICACY - Upik Tria; Kuswardi, Yemi; Sutopo, Sutopo (TRANSFORMASI, 2024)
The purpose of this study was to determine the effect of applying the Make a Match learning model with and without puzzles on critical thinking skills by reviewing self-efficacy. All students of SMP Negeri 4 Karanganyar 2023/2024 class VIII became the research population, and students in class VIIIA, B, and F were selected using a cluster random sampling technique as samples. Learning models, puzzle media, and self-efficacy are determined as independent variables, while thinking skills are determined as dependent variables. Data was collected using documentation, tests, and questionnaire techniques. The hypothesis was tested by two-way ANOVA on different cells. This research can show that the application of the Make a Match learning model with and without puzzles has a positive effect on critical thinking skills in the Pythagorean theorem material with an increase in average scores of 90.078 and 87.344. The level of self-efficacy has a positive effect on critical thinking skills with an increase in the average score of 87.765 for high self-efficacy students. Apart from that it can also be seen that the effect of providing a learning model on critical thinking skills does not depend on self-efficacy, and vice versa. The Make a Match learning model can be applied to other material with modifications according to student needs, or carried out using technology to improve critical thinking skills.